A clinical study on varicose veins of lower limb, surgical management and functional outcome at a tertiary care hospital of South India - Nageswara rao, Bandaru; Pushpalatha, Ramachandra (International Surgery Journal, 2020)
Background: Varicose veins defined as dilated, tortuous, subcutaneous veins ≥3 mm in diameter, measured in the upright position with demonstrable reflux. Though the history of varicose veins dates prehistorically, the advances in diagnosis and new management modalities gained attention recently. The aim of the present study was to study the clinical profile, risk factors and their association, different types of surgical procedures employed and complications associated with varicose veins. Methods: A one year observational after ethical committee approval was conducted by department of general surgery at ACSR Medical College. Cases fulfilling the inclusion criteria were clinically examined and duplex ultrasound colour Doppler was performed for diagnosing the varicose veins and findings of site of incompetence was noted. All the cases were operated and followed up for six months period. The results were tabulated and analyzed in Microsoft Excel for any corrections. Results: Eighty cases with 66.25% males and 33.75% females with mean age of 40.24 years and majority (40%) were in 41 to 50 years group. 60% of cases had varices in right limb and long saphenous vein was involved in 52.5% of cases.85% had dilated veins, perforator incompetence was noted below the knee in 30% of cases. 41.25% of cases saphenofemoral flush ligation with stripping of long saphenous vein. Wound infection was the common postoperative complication. Conclusions: Operative line of management should be the first line of treatment even though conservative management relieves the symptoms but always requires a definitive management.